2023
DOI: 10.1158/1078-0432.c.6523718
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from PD-1 Blockade Boosts Radiofrequency Ablation–Elicited Adaptive Immune Responses against Tumor

Abstract: <div>Abstract<p><b>Purpose:</b> Radiofrequency ablation (RFA) has been shown to elicit tumor-specific T-cell immune responses, but is not sufficient to prevent cancer progression. Here, we investigated immune-suppressive mechanisms limiting the efficacy of RFA.</p><p><b>Experimental Design:</b> We performed a retrospective case-controlled study on patients with synchronous colorectal cancer liver metastases who had received primary tumor resection with or without… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As a result, combined techniques to improve CRC therapy effectiveness have become critical. Anti-PD-1/ anti-PD-L1 combined with anti-CTLA4 drugs, locoregional treatments, or VEGF/VEGFR inhibitors, for example, boosts anti-tumor immunity synergistically [31][32][33]. These findings suggested that anticancer drugs that stimulate tumor immunity, when combined with anti-PD-1/anti-PD-L1 antibodies, might provide show encouraging effects.…”
Section: Discussionmentioning
confidence: 94%
“…As a result, combined techniques to improve CRC therapy effectiveness have become critical. Anti-PD-1/ anti-PD-L1 combined with anti-CTLA4 drugs, locoregional treatments, or VEGF/VEGFR inhibitors, for example, boosts anti-tumor immunity synergistically [31][32][33]. These findings suggested that anticancer drugs that stimulate tumor immunity, when combined with anti-PD-1/anti-PD-L1 antibodies, might provide show encouraging effects.…”
Section: Discussionmentioning
confidence: 94%